Assessment of human fetal cardiac autonomic nervous system development using color tissue Doppler imaging. Issue 6 (21st May 2021) - Zwanenburg, Fleur; Jongbloed, Monique R. M.; van Geloven, Nan; ten Harkel, Arend D. J.; van Lith, Jan M. M.; Haak, Monique C.
Abstract: Objectives: Functional development of the fetal cardiac autonomic nervous system (cANS) plays a key role in fetal maturation and can be assessed through fetal heart rate variability (fHRV)‐analysis, with each HRV parameter representing different aspects of cANS activity. Current available techniques, however, are unable to assess the fHRV parameters accurately throughout the whole pregnancy. This study aims to test the feasibility of color tissue Doppler imaging (cTDI) as a new ultrasound technique for HRV analysis. Secondly, we explored time trends of fHRV parameters using this technique. Methods: 18 healthy singleton fetuses were examined sequentially every 8 weeks from 10 weeks GA onwards. From each examination, 3 cTDI recordings of the four‐chamber view of 10 seconds were retrieved to determine accurate beat‐to‐beat intervals. The fHRV parameters SDNN, RMSSD, SDNN/RMSSD, and pNN10, each representing different functional aspects of the cANS, were measured, and time trends during pregnancy were explored using spline functions within a linear mixed‐effects model. Results: In total, 77% (95% Cl 66–87%) of examinations were feasible for fHRV analysis from the first trimester onwards, which is a great improvement compared to other techniques. The technique is able to determine different maturation rates of the fHRV parameters, showing that cANS function, presumably parasympathetic activity, establishes around 20 weeks GA and matures rapidly until 30 weeks GA. Conclusions: This is the first study able to assess cANS function through fHRV analysis from the first trimester onwards. The use of cTDI to determine beat‐to‐beat intervals seems feasible in just 3 clips of 10 seconds, which holds promise for future clinical use in assessing fetal well‐being.